Optimalisasi Media Pembelajaran Berbasis Teknologi dan Buku Ajar dalam Pengajaran Pendidikan Agama Islam di SMP Muhammadiyah 57 Medan - Yuspan Jailani Lubis; Rizka Harfiani (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to optimize the use of technology-based learning media and textbooks in the teaching of Islamic Religious Education at SMP Muhammadiyah 57 Medan. The current issue in learning is the limited utilization of technology that supports effective learning interaction and the lack of media variety used in delivering material. This research employs a qualitative method through observation, interviews, and document analysis. The findings reveal that the use of technology-based media such as infocus, laptops, and visual materials significantly improves students' understanding of Islamic Religious Education topics. Textbooks still play a crucial role as a primary supporting medium, but integration with technology results in a more dynamic and engaging learning interaction. Challenges include limited infrastructure and teacher training, but these can be addressed with school management support and continuous professional development.